74 Mechanistic Study for the role of advanced glycation end products in the development of diabetic heart failure. (9th June 2011) - Hegab, Z; Mohammed, T M A; Neyses, L; Mamas, M
Abstract : Advanced glycation end products (AGEs) are thought to play a crucial role in the development of diabetic complications including heart failure, a leading cause of morbidity and mortality in diabetic patients. However, the molecular mechanisms that underlie the pathophysiological contribution of AGEs to heart failure development are not yet fully understood. We therefore investigated the effects and mechanisms of action of AGEs on isolated neonatal rat cardiomyocytes (NRCM). Standard molecular techniques were applied. Western blot showed that RAGE receptor is expressed in NRCM and adult mouse cardiomyocytes. Incubation of NRCM for 24 h with AGEs showed a dose dependant reduction of calcium transient amplitude with a maximum of 52% at 1 g/l (p<0.01) accompanied with 32% reduction in SR calcium content with no significant changes in the protein expression of calcium handling proteins. We demonstrated a 24% increase (p<0.01) in the production of reactive oxygen species ROS in AGE treated cardiomyocytes mediated through increased NADPH oxidase activity (p<0.05). Subsequent translocation of NF-KB, a transcriptional factor from the cytoplasm to the nucleus together with increased NF-KB activity resulted in a 56% increase in iNOS gene protein expression (p<0.01), a downstream target of NF-KB. The latter was associated with 10% increase in NO production (p<0.05) with subsequent nitrosylation of the Ryanodine receptor shown through immunofluoresence. Changes in calcium transient were completely inhibited when we incubated the cardiomyocytes with inhibitors of NADPH oxidase, NOS or NF-KB prior to their incubation with AGEs. In conclusion, AGEs directly decline cardiomyocytes function through binding to their RAGE receptor leading to calcium handling impairment through increased ROS production inducing activation and translocation of NF-KB to the nucleus. The latter increased transcription of iNOS with increased NO production. Coexistence of ROS and NO favours the production of peroxynitrite that is capable of nitrosylation of key cellular proteins such as the Ryanodine receptor that has a crucial role in cardiac excitation-contraction coupling. This study provides novel insights into the mechanisms of cardiac damage in diabetes that occur independent of vascular disease through AGEs.